Peran Asupan Omega-3, Status Gizi, dan Kualitas Tidur dalam Meningkatkan Konsentrasi Belajar Anak Usia Sekolah Dasar di SDIT Bina Muda Cicalengka - Utami, Sherina Putri; Riana, Asysyifa; harun, iriyanti (Institut Kesehatan Immanuel, 2025)
Learning concentration is an important aspect in achieving student learning outcomes that can be influenced by various factors such as environment, family support, omega 3 intake, and sleep duration. This study aims to determine the relationship between omega 3 intake, nutritional status, and sleep duration with student learning concentration at SDIT Bina Muda Cicalengka. This type of research uses quantitative analytic observational with cross-sectional design on 92 students aged 10-12 years taken by total sampling. Data were analyzed using the Chi-square test. The majority of respondents were 11 years old (44.6%), male (52.2%), had more omega 3 intake (47.8%), normal nutritional status (75%), less sleep duration (66.3%), and low learning concentration (48.9%). The results showed that there was no significant relationship between omega 3 intake (p = 0.725) and nutritional status (p = 0.258) with learning concentration, but there was a significant relationship between sleep duration (p = 0.000) with learning concentration. It can be concluded that sleep duration plays an important role in improving students learning concentration. It is recommended that students have to maintain their sleep duration of 9-11 hours per night and schools have to provide the education to parents about the importance of adequate sleep.